Analisis Faktor-Faktor yang Mempengaruhi Konversi Lahan Pertanian Sawah ke Non Pertanian di Kabupaten Banyumas Jawa Tengah - Kusnaman, Djeimy; Elyanto, Adwi Herry Koesoema; Mandamdari, Alpha Nadeira (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Agricultural land in Banyumas Regency has decreased from year to year due to population and economic growth. The farm rice fields in Banyumas Regency in 2017 were 66.210 hectares, reduced to 63.326 hectares in 2020 or decrease in land area of 4%. This research was aimed to examine the conversion rate of agricultural land in the Banyumas Regency and factors that determine the conversion of agricultural land in the Banyumas Regency. The primary method used was descriptive-analytical. Determination of the research location was using a purposive method in Banyumas Regency. The technique to analyze the data was Linear multiple regression (Ordinary Least Squares). The information which used in this research was secondary data in 2010 – 2020. The variables in this research are conversion of agricultural land, population, number of industries, Gross Regional Domestic Product (GRDP), and Farmer’s terms of trade (FTT). This research shows that the conversion rate of agricultural land in Banyumas Regency is 8,45%, meaning that the average of arm rice fields in Banyumas regency for the last ten years (2010 – 2020) has decreased by 8,45%. The multiple linear regression analysis shows that the variables number of population, number of industry, and Gross Regional Domestic Product (GRDP) have a significant and positive effect on the conversion of agricultural land in Banyumas Regency. Farmer’s terms of trade (FTT) do not significantly affect agricultural land conversion in Banyumas Regency.